Radiofrequency Ablation of the Pancreas: Protective Effect of Local Cooling Techniques. Issue 5 (May 2015) - Geranios, Angelos; Pikoulis, Emmanouil; Papalois, Apostolos; Kontos, Michael; Agrogiannis, George; Petrou, Athanasios; Pavlakis, Emmanuel; Felekouras, Evangelos
Pancreatic carcinoma is one of the commonest malignant diseases today and the majority of patients are suitable for palliative treatment only. Radiofrequency ablation (RFA) has been used extensively for the treatment of solid organ tumors but little is known on the efficacy and safety of pancreatic ablation. To further investigate the safety of pancreatic RFA, 18 pigs had RFA of the pancreas, close to superior mesenteric vein and duodenum. Group A (nine animals) was protected with peripancreatic cool perfusion and Group B (nine animals) with portal vein (PV) intravenous injection of cool saline. Biochemical and histological evidence suggested lateral thermal injury of the duodenal wall and superior mesenteric vein and acute pancreatitis in most animals. However, clinically and at autopsy, Group B animals fared much better. PV thrombosis, hepatic abscess, duodenal perforation, ascites, and extensive pancreatic necrosis were observed in Group A but not in Group B. The present study suggests that PV cool saline perfusion can prevent major complications caused by pancreatic RFA and may be used in combination with other protective techniques in the clinical setting to reduce RFA-associated morbidity.